Recent Advances in Anode Metallic Catalysts Supported on Conducting Polymer-Based Materials for Direct Alcohol Fuel Cells - Halim, El Mahdi; Chemchoub, Sanaa; El Attar, Anas; Salih, Fatima Ezzahra; Oularbi, Larbi; EL RHAZI, Mama (Frontiers in Energy Research, 2022)
Sustainable energy development is a major challenge, particularly when considering population increase, rising energy demands resulting from the excessive use of nonrenewable fossil fuels, and growing consequences on global pollution and climate change. It is critical to continue to develop new sources of renewable and clean energy. Direct Alcohol Fuel cell (DAFC) represents a technological approach that meets all the requirements in terms of energy conversion with good electrical efficiency and lower emissions of pollutants. However, it largely suffers from the poisoning of the anode catalyst caused by the accumulation of intermediate products. In this context, this review is devoted to discussing the recent progress in anode catalysts based on conducting polymers (CPs) materials for direct alcohol fuel cells, especially direct methanol and ethanol fuel cells, from the viewpoint of synthesis techniques, morphology, and catalytic performance. In the first part of this review, we will explore the most commonly used methods for preparing metal-conducting polymer-based nanocomposites, including the key factors influencing their morphology regardless of the application. The catalytic performances of mono-, bi-, and tri-metal catalysts deposited on conducting polymer-based supports for the electrooxidation of methanol and ethanol reactions are examined in detail in the second and third parts of this review. We also highlight the effect of the introduction of carbon nanomaterials into conducting polymer supports on the electrical properties and on the performance of the catalysts. Development of anode materials using nanostructured conducting polymers-based support plays a vital role in reducing catalyst loadings and should therefore shed light on the wide-scale commercialization of DAFCs. In a nutshell, this review will give readers a thorough understanding of the principles of direct alcohol fuel cells, new advancements in electrode materials based on non-precious metals and the main challenges that should be dealt with.